STRATEGI MENJADI PERUSAHAAN YANG SEMAKIN SOSIAL - DICKY SUPRIATNA (Media Bisnis, 2014)
Enterprise social software will become a major application in the strategy into a social enterprise. ESS is able to support every user to carry out a notice, consideration or action on the relevant information to carry out the work routine and non routine. However, in its application, and the ESS should be supported by a deep understanding and strong commitment from management.